2011
DOI: 10.1103/physrevb.84.153302
|View full text |Cite
|
Sign up to set email alerts
|

Acetic acid on silicon (001): An exercise in chemical analogy

Abstract: Using the acetic acid/Si(001) system as an illustrative example, we discuss the limits and opportunities of "chemical analogy" as a paradigm to rationalize chemisorption processes on surfaces. Recent proposals that acetic acid chemisorption results in a bidentate, single-dehydrogenated product are based on earlier findings for the acetic acid/Ge(001) system. In contrast, the well-characterized reaction of acetone with Si(001) suggests that acetic acid chemisorption leads to the loss of two hydrogen atoms from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…15 This is a direct result of the Ge-O and Ge-C bonds that link the adsorbate moieties to the Ge(001) substrate being signicantly weaker than the corresponding Si-O and Si-C bonds. Similar conclusions can be drawn by comparing the adsorption energies of acetic acid 38 and the unsaturated hydrocarbons acetylene, ethylene and benzene 21 on the Si(001) and Ge(001) surfaces. Our results are also consistent with earlier work on the adsorption of 1,3-butadiene on Si(001) and Ge(001) which showed that the Ge-C bonds were 0.26-0.33 eV weaker than the corresponding Si-C bonds.…”
Section: Comparison Between Acetone Adsorption On Ge(001) and Si(001)supporting
confidence: 73%
“…15 This is a direct result of the Ge-O and Ge-C bonds that link the adsorbate moieties to the Ge(001) substrate being signicantly weaker than the corresponding Si-O and Si-C bonds. Similar conclusions can be drawn by comparing the adsorption energies of acetic acid 38 and the unsaturated hydrocarbons acetylene, ethylene and benzene 21 on the Si(001) and Ge(001) surfaces. Our results are also consistent with earlier work on the adsorption of 1,3-butadiene on Si(001) and Ge(001) which showed that the Ge-C bonds were 0.26-0.33 eV weaker than the corresponding Si-C bonds.…”
Section: Comparison Between Acetone Adsorption On Ge(001) and Si(001)supporting
confidence: 73%
“…Determining the adsorption structures of organic molecules on the technologically important Si(001) surface is an important fundamental step toward this goal. [5][6][7][8][9][10][11][12][13][14] Recent advances in atomic-scale imaging, photoelectron and X-ray absorption spectroscopy, and theoretical calculations now provide us with the ability to determine the structure of surface adsorbates with atomic-scale precision. Scanning tunnelling microscopy (STM) can provide atomically-resolved images of individual adsorbates, often resolving key features that are critical to the correct identification of the structures.…”
Section: Introductionmentioning
confidence: 99%
“…These range from controlling reaction mechanisms [6], on-surface synthesis [7], self-assembly for molecular electronics device construction [8], to surface functionalization [9] and the use of such surfaces as templates [5]. Atomistic simulations, in particular density functional theory (DFT) and techniques beyond have a proven track record of resolving experimentally observed structures, and the electronic structure of such systems, as well as predicting configurations that have yet to be confirmed experimentally [10][11][12].…”
mentioning
confidence: 99%